Transforming Museum Management : Evidence-Based Change through Open Systems Theory. - Jung, Yuha ([Place of publication not identified] : Routledge, 2021)
Museums must change to illuminate the histories, cultures, and social issues that matter to their local population. Based on a unique longitudinal ethnographic study, Transforming Museum Management illustrates how a traditional art museum attempted to transform into a more inclusive and community-based institution. Using open systems theory and the Buddhist concept of mutual causality, it examines the museum's internal management structure and culture, programs and exhibitions, and mental models of museum workers. In providing both theoretical and practical foundations to transform management structures, thisaccessible volume will benefit stakeholders by proposing a new culture and structure to arts institutions, to change practice to be more relevant, diverse, and inclusive. This book will be an invaluable resource for researchers and advanced students of museum studies, cultural management, arts administration, non-profit management, and organizational studies.
List of FiguresPrefaceAcknowledgmentsChapter One: Introduction to Research and MethodologyChapter Two: Open Systems Theory and Mutual CausalityChapter Three: Entangled Realities between the Museum and Its CommunityChapter Four: Museum Throughputs and Mental Models Chapter Five: Outputs and Outcomes of Museum ChangeChapter Six: Toward a Deep Learning Museum and Paradigm ShiftAppendix A: List of Key Participants' Pseudonyms and Their AffiliationsIndex
OCLC-licensed vendor bibliographic record.
Keywords: Museums -- Management; System theory; Organizational change; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Museum Administration & Museology